Potencial de conservação de queijo coalho com o uso de cobertura a base de soro e conservante natural e sintético - Souza, Lara Barboza de (2020)
Coalho cheese is a dairy derivative rich in nutrients, with proteins of high biological value, characterized as medium to high humidity, soft texture and slightly acidic. These conditions can favor microbial contamination. Food coating appears as a tool for conservation technology, in which films and coverings can prolong the freshness characteristics of the food. The objective was to develop an edible coating based on cheese whey and to analyze the influence on the shelf life of coalho cheese and the impact of cold storage on the organoleptic characteristics of the food. For this, the study was divided into two distinct and complementary stages, composed of two experiments. In experiment I, the film-based serum-based solution was prepared and six coatings formulations were tested, carrying out microbiological characterization (aerobic mesophiles, coliforms at 35 ° and 45 °, filamentous fungi and yeasts, Staphylococcus sp. and Salmonella sp.) physics analysis (pH, color and texture) of the coalho cheese samples. In experiment II, samples of coalho cheese were evaluated during 20 days of cold storage at 5ºC, at five day intervals (production day =T0, five days = T5, ten days = T10, 15 days = T15 and twenty days = T20 ), with two active coatings made with serum, gelatin (10%) and starch (10%), and addition of nisin in coating 1 (QR1) and probiotic strains in coating 2 (QR2). After coating and forming the cover, the samples were submitted to microbiological analyzes (total count of aerobic mesophilic bacteria, positive coagulase Staphylococcus count and Salmonella sp. Research), determination of pH, color and texture profile (firmness, elasticity, cohesiveness, guminess and chewability). The microbial count of the control cheese was higher throughout the analysis period. The coating showed potential for application as a barrier to contaminants in cheese, in addition to maintaining its freshness characteristics. Changes in the consistency of the dough were significant after 15 days of cold storage. The bioactive edible covering showed potential application to the conservation of rennet cheese and allowed greater stability of the food